Persepsi Pengasuh dalam Pola Asuh dan Pemberian Makan pada Anak dengan Cerebral Palsy - Syarifah Nur Zakiyah (Syntax Corporation Indonesia, 2024)
Cerebral palsy (CP) is a neurological disorder that affects a child's motor skills and motor skills, which often causes difficulties in parenting and feeding. This study aims to explore the perception of caregivers related to parenting and feeding in children with CP at the Jakarta Disabled Children Development Foundation (YPAC). The research uses a qualitative method with in-depth interviews with caregivers and educators at YPAC. The results of the study show that caregivers tend to apply a responsive parenting style aimed at increasing children's independence, although this process takes a long time. In feeding, caregivers face challenges such as food rejection, physical limitations in chewing and swallowing, and proper feeding positioning. In conclusion, caregiver support plays a very important role in improving the quality of life of CP children, both in terms of independence and proper nutritional intake. Training and support for caregivers is important to deal with these challenges more effectively.